Teachers of Pilipino in the division of Cotobato I and their teaching difficulties - Trinidad, Herminigildo D. 1917-
The purpose of the study is to determine the characteristics of primary grades teachers teaching Pilipino in the Division of Cotabato I for the school year 1972-1973. It attempts to know the following: the characteristics of the teachers teaching Pilipino in terms of their personal data, regional origin, academic units earned in Pilipino and in-service education in this language; the instructional difficulties of teachers as to the use of Pilipino as medium of instruction, instructional materials, and methods of teaching this language; and the discernible attitude of parents, teachers, school administrators and pupils toward the use of Pilipino as medium of instruction in the primary grades.